2011
DOI: 10.4049/jimmunol.1002989
|View full text |Cite
|
Sign up to set email alerts
|

Both miR-17-5p and miR-20a Alleviate Suppressive Potential of Myeloid-Derived Suppressor Cells by Modulating STAT3 Expression

Abstract: Myeloid-derived suppressor cells (MDSCs) were one of the major components of the immune suppressive network. STAT3 has an important role in regulating the suppressive potential of MDSCs. In this study, we found that the expression of STAT3 could be modulated by both miR-17-5p and miR-20a. The transfection of miR-17-5p or miR-20a remarkably reduces the expression of reactive oxygen species and the production of H2O2, which are regulated by STAT3. MDSCs transfected with miR-17-5p or miR-20a are less able to supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
129
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(131 citation statements)
references
References 39 publications
1
129
0
1
Order By: Relevance
“…[35][36][37] STAT3 has also been found to be a target of miR-17 and miR-20a in mouse ES cells and mouse myeloid-derived suppressor cells. 38,39 Here, we show that miR-17 and miR-20a can target the p21 and STAT3 3 0 UTR to inhibit the expression of p21 and STAT3 in human cells. STAT3 exists in two isoforms, STAT3a and STAT3b, and they share a similar 3 0 UTR sequences.…”
Section: Discussionmentioning
confidence: 74%
“…[35][36][37] STAT3 has also been found to be a target of miR-17 and miR-20a in mouse ES cells and mouse myeloid-derived suppressor cells. 38,39 Here, we show that miR-17 and miR-20a can target the p21 and STAT3 3 0 UTR to inhibit the expression of p21 and STAT3 in human cells. STAT3 exists in two isoforms, STAT3a and STAT3b, and they share a similar 3 0 UTR sequences.…”
Section: Discussionmentioning
confidence: 74%
“…It has been reported that miRNAs, including miR-17-5p, miR-20a (30), miR-223 (31), and miR-494 (32), are involved in regulating the differentiation and function of tumor-expanded MDSCs. miR-17-5p and miR-20a alleviate the immunosuppressive potential of MDSCs by modulating STAT3 expression (30). Additionally, miR-223 suppresses differentiation of tumor-induced MDSCs from bone marrow cells via targeting MEF2C.…”
Section: Discussionmentioning
confidence: 99%
“…miR-17-5p and miR-20a are expressed at low levels in myeloid-derived suppresser cells and alleviate the suppressive function of myeloid-derived suppresser cells by targeting the transcription factor STAT3. 85 Peroxisome proliferatoractivated receptor c (PPARc) expression is reduced after LPS stimulation due to miR-27b induction, which directly targets PPARc mRNA. 63 Inhibition of miR-27b increased PPARc expression and thus resulted in the reduced production of pro-inflammatory cytokines from LPS-stimulated macrophages.…”
Section: Mirnas In Regulation Of Tlr and Rig-i Pathways Yk LI And Xy mentioning
confidence: 99%